(untitled) (Journal of Hama University, 2022)
The appearance of gummy smile is a common problem in some people, and the appearance of pink color causes concern for many people, which prompted the researchers to develop various surgical techniques that took care of managing the problem of the gummy smile, including the process of convetional of lip repositioning with appearance of lasers in surgeries, that process was modified and undoubtedly In it. Effectiveness evaluation the use of the Erbium Yag laser in the conventional and modified lip repositioning process. It is a prospective study of male average age of 26 years, were made to the lip repositioning for this patient by modified technique (by using Erbium Yag laser for left side of the patient and by using surgical scalpel for right side of the patient) and The measurements were made as follows: bleeding first 24 hours, pain and swelling for a week after surgery, discomfort for a month, recurance after 6 weeks, 3 months, and 6 months. statistically significant differences were found on the level, But he did not notice significant differences during the first three months between the two groups. The use of the Erbium Yag laser in the lip repositioning process proved that it was able to overcome the complications following the use of the surgical scalpel in the same process.